2013
DOI: 10.1016/j.jagp.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Cognitive Behavioral Social Skills Training for Older Consumers With Schizophrenia: Defeatist Performance Attitudes and Functional Outcome

Abstract: Objectives To determine whether cognitive behavioral social skills training (CBSST) is an effective psychosocial intervention to improve functioning in older consumers with schizophrenia, and whether defeatist performance attitudes are associated with change in functioning in CBSST. Design An 18-month, single-blind, randomized controlled trial. Setting Outpatient clinic at a university-affiliated Veterans Affairs hospital. Participants Veteran and non-veteran consumers with schizophrenia or schizoaffecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 35 publications
6
108
2
3
Order By: Relevance
“…Specifically, given that the interventions used in this study did not directly target negative beliefs about success, those with low levels of expectancies of success may benefit from techniques or interventions that focus on modifying beliefs to reduce negative symptoms (e.g. Grant et al, 2012;Granholm et al, 2013). Alternatively, given the identified links between low metacognitive capacity and both reduced intrinsic motivation (Vohs and Lysaker, 2014) and concurrent and prospective negative symptoms (Tas et al, 2012;McLeod et al, 2014) it may be that those with lower baseline expectancies of success would benefit from an integrated psychotherapy that aims to develop the degree to which persons form complex and integrated ideas about themselves, their future, and their goals (Lysaker et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, given that the interventions used in this study did not directly target negative beliefs about success, those with low levels of expectancies of success may benefit from techniques or interventions that focus on modifying beliefs to reduce negative symptoms (e.g. Grant et al, 2012;Granholm et al, 2013). Alternatively, given the identified links between low metacognitive capacity and both reduced intrinsic motivation (Vohs and Lysaker, 2014) and concurrent and prospective negative symptoms (Tas et al, 2012;McLeod et al, 2014) it may be that those with lower baseline expectancies of success would benefit from an integrated psychotherapy that aims to develop the degree to which persons form complex and integrated ideas about themselves, their future, and their goals (Lysaker et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal investigations of defeatist performance beliefs in individuals with schizophrenia have largely been conducted in the context of cognitive therapy clinical trials, which have found some support for an association between a reduction in defeatist performance beliefs and improved negative symptoms and functioning over time (Granholm et al, 2013;Granholm et al, 2014). However, the longitudinal relationship between negative symptoms and other types of dysfunctional beliefs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Defeatist performance beliefs have been assessed in inpatients and outpatients with schizophrenia [13,16], older adults with schizophrenia [19], individuals with deficit syndrome schizophrenia [20], those with recent on-set schizophrenia [15], and veterans with schizophrenia [14]. Despite considerable research in schizophrenia samples, there is a dearth of research investigating defeatist performance beliefs in individuals with schizotypy.…”
Section: Defeatist Beliefs In Schizotypymentioning
confidence: 99%
“…In response, CBT interventions have begun to arise that emphasize correcting unhelpful cognitions and tailor behavioral strategies directly pertinent to deficits in functioning. For example, interventions for persons with severe mental illness combining CBT with social skills training that include content adapted for interpersonal settings have demonstrated positive benefits over time with regard to independent living skills and social skills acquisition (Granholm et al, 2013).…”
Section: Introductionmentioning
confidence: 99%